2021
DOI: 10.1093/eurjcn/zvab005
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Nurse Led Transitional Care Model on elderly patients undergoing open heart surgery: a randomized controlled trial

Abstract: Aims  Rate and number of successful cases in open heart surgery has been increasing due to the advances in medical technology and surgery. To improve patient convalescence results and reduce rate of post-discharge readmission to hospital and unplanned post-discharge rehospitalization, home-care and follow-up process of patients should be managed successfully. To evaluate the effectiveness of Nurse Led Transitional Care Model on the functional autonomy, quality of life, readmission, and rehosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 29 publications
0
31
0
9
Order By: Relevance
“…Likewise, a randomized controlled trial assessed nurse-led TC for old people with open heart surgery. It was suggested that patient's life quality and functional autonomy are markedly increased, while rehospitalization and hospital readmission rates after discharge are conspicuously decreased [ 22 ]. TC also improves acute attack patient's life quality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a randomized controlled trial assessed nurse-led TC for old people with open heart surgery. It was suggested that patient's life quality and functional autonomy are markedly increased, while rehospitalization and hospital readmission rates after discharge are conspicuously decreased [ 22 ]. TC also improves acute attack patient's life quality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…20 Additional studies revealed successful outcomes of 7-to 10-day postdischarge phone calls. 18,20,22 Given the signifi cance of 30-day readmissions in relation to increased mortality and healthcare costs and decreased quality of life of individual patients and families, implementing postdischarge telephone followup calls within 7-10 days of discharge is essential.…”
mentioning
confidence: 99%
“…A cohort study emphasized the importance of timely follow-up calls to reduce 30-day readmission rates; the critical window for readmission is the first 2-3 weeks after discharge, with a median time of readmission at 11 days 20. Additional studies revealed successful outcomes of 7- to 10-day postdischarge phone calls 18,20,22. Given the significance of 30-day readmissions in relation to increased mortality and healthcare costs and decreased quality of life of individual patients and families, implementing postdischarge telephone follow-up calls within 7-10 days of discharge is essential.…”
mentioning
confidence: 99%
See 2 more Smart Citations